Vocational Awareness, Aspiration, and Career Readiness of Aviation Students in the Industry 5.0 Era - Femmy Sofie Schouten; Avi Mukti Amin; Edy Kurniawan; Subarto Subarto; Siti Khadijah Koto; Torang Hutabarat; Anasta Wirawan; Sulistyo Sutanto (Indonesia Civil Pilot Academy Banyuwagi, 2026)
The Industry 5.0 paradigm emphasizing human-technology collaboration, sustainability, and resilience demands a reconceptualization of career readiness in vocational aviation education. However, empirical research on how vocational awareness and vocational aspiration jointly shape aviation students' career readiness within this new paradigm remains limited, particularly in the Indonesian context. This quantitative, cross-sectional survey involved 184 aviation students from four academies in Java (sampled from 350 using proportional stratified random sampling). Validated Likert-scale instruments (Cronbach's ? > 0.85) measured all constructs, and data were analyzed using multiple linear regression. The results showed that vocational awareness (? = 0.476, p < 0.001) and vocational aspiration (? = 0.351, p < 0.001) jointly explained 67.3% of the variance in career readiness (R² = 0.673, F = 189.23, p < 0.001), with awareness exerting a significantly stronger effect. Theoretically, this study extends Social Cognitive Career Theory to the Industry 5.0 context; practically, it underscores the urgent need for human-centric industry induction and career guidance programs in aviation academies.